A green, efficient, closed-loop direct regeneration technology for reconstructing of the LiNi0.5Co0.2Mn0.3O2 cathode material from spent lithium-ion batteries - Fan, Xiaoping; Tan, Chunlei; Li, Yu; Chen, Zhiqiang; Li, Yahao; Huang, Youguo; Pan, Qichang; Zheng, Fenghua; Wang, Hongqiang; Li, Qingyu (Journal of hazardous materials, 2021)
Lithium nickel manganese cobalt oxide in the spent lithium ion batteries (LIBs) contains a lot of lithium, nickel, cobalt and manganese. However, how to effectively recover these valuable metals under the premise of reducing environmental pollution is still a challenge. In this work, a green, efficient, closed-loop direct regeneration technology is proposed to reconstruct LiNi0.5Co0.2Mn0.3O2 (NCM523) cathode materials from spent LIBs. Firstly, the failure mechanism of NCM523 cathode materials in the spent LIBs is analyzed deeply. It is found that the spent NCM523 material has problems such as the dissolution of lithium and transition metals, surface interface failure and structural transformation, resulting in serious deterioration of electrochemical performance. Then NCM523 material was directly regenerated by supplementing metal ions, granulation, ion doping and heat treatment. Meanwhile, PO43− polyanions were doped into the regenerated NCM material in the recovery process, showing excellent electrochemical performance with discharge capacity of 189.8 mAh g−1 at 0.1 C. The recovery process proposed in this study puts forward a new strategy for the recovery various lithium nickel cobalt manganese oxide (e.g., LiNi1/3Co1/3Mn1/3O2, LiNi0.5Co0.2Mn0.3O2, LiNi0.6Co0.2Mn0.2O2 and LiNi0.8Co0.1Mn0.1O2) and accelerates the industrialization of spent lithium ion battery recycling. [Display omitted] •A direct regeneration technology is proposed to reconstruct NCM523 cathode materials from spent LIBs.•The failure behaviors of the LiNi0.5Co0.2Mn0.3O2 of spent LIBs were analyzed in depth.•The specific discharge capacity of the reconstructed RNCMP-2 material is as high as 189.8 mAh g−1 at 0.1 C rate.